Review of approaches to identifying and forming lists of strategic minerals and critical raw materials in Ukraine - S. F. Lytvyniuk; M. S. Burlutskyy (Мінеральні ресурси України)
Importance and themes of this article are determined by the political, economic, regulatory and technological “attention” to critical (strategic) mineral raw materials (CRMs) and products from them on the global and regional economic scale. Transition to Low-Carbon circular economy, resource-efficient production and high environmental standards (ESG criteria) applied to various processes, on the one hand, stipulate an increase in demand for mineral raw materials used in “green transition” technologies, as confirmed by the World Bank, while, on the other hand, it accelerates adaptation and restructuring of regulatory policies (strategies) for resource management in countries that own critical raw materials (CRMs) or use them in large quantities. As part of the research, various approaches and methods to defining and forming the lists of critical raw materials (minerals, elements) that exist in the world and Ukraine were analyzed. The unification of such approaches for economically connected regions is a way to create reliable supply chains of CRMs for sustainable development within the interaction framework (economic, technological, environmental, etc.). Following from results of the research, the authors attempted to define comprehension of strategic/critical raw materials and minerals basing on lists from the European Union (EU) and Ukraine. The concept criticality in the field of subsoil use was introduced by recent changes to the Ukrainian legislation. The lists of critical raw materials and minerals from Ukraine and the EU were compared. It is concluded that definitions differ and complicated as a consequence of dissimilar approaches applied to formulate, define and group materials, minerals and elements (ore, compound, component) to be critical for their economies their grouping. Research methodology developed as well as list of strategic/critical mineral raw materials developed in this article can be used for reforming the regulatory framework of Ukraine in the field of subsoil use.